Empowering dyslexic children’s literacy through mobile applications and multisensory: enhancing the main 4Cs of 21st century learning skills in narrative writing / Raganeswari Ramasamy, Dr. Mariam Mohamad and Ts. Dr. Mageswaran Sanmugam - Ramasamy, Raganeswari; Mohamad, Mariam; Sanmugam, Mageswaran (Universiti Teknologi MARA, Kedah, 2023)
English proficiency is vital to develop a knowledgeable society. Nevertheless, upper secondary students still face major problems in writing skills, such as developing main ideas, organizing the ideas into a few paragraphs, as well as using the correct grammar and vocabulary elements to produce a good story. Therefore, this study introduces a writing module which was ‘4Cs to WRITE’ as a step-by-step guideline to enable upper secondary students to improve their narrative writing skills by using an online learning platform via mobile devices. This was a mixed-method study in which the data were collected from 55 upper-secondary students from two different schools in Malaysia. The data were collected by using pre-test and post-test, participant observation, document analysis, and focus group interview. The outcomes of the treatment revealed that the mean scores in the post-tests of the narrative essay improved in both schools. The results indicated that the potential of using a writing module could be implemented to teach different types of writing skills for upper secondary school students. Moreover, this could develop their overall writing abilities as the classroom practices for writing skills are inadequate due to the time constraints and the teachers need to focus on other three skills.